Knowledge, Attitude and Practices Regarding Muscular Reinforcement among Judokas in Developing Countries: Case Study of the Republic of Benin - Polycarpe Gouthon; Jean-Paul Kouassi; Kouame N'Guessan; Issiako Bio-Nigan; Brigitte Tonon; Basile Nouatin; Léonce Linta; Jean-Marie Falola; Barnabé Akplogan (The Society of Aging and Physical Activity (SAPA), 2015)
This cross-sectional survey determined the level of knowledge, attitude, and practice about muscular reinforcement (MR) among judokas in the Republic of Benin as typical of a developing country. It also examined the relations between the levels of knowledge, attitude, and practice among these judokas. It was undertaken using a non-probabilistic and exhaustive sample of 79 judokas in the cities of Cotonou and Porto-Novo having a minimum rank of green belt. The levels of knowledge, attitude, and practice were assessed by a questionnaire that comprised 43 items. Information relating to the socio-demographic characteristics and judo practice of the participants were also acquired. The levels among the surveyed judokas were low for knowledge (62 78.5%), attitude (49 62.0%), and practice (49 62.0%). The level of knowledge was significantly associated with attitude and practice for MR (x2= 3.99 p = 0.04 Cramer's V = 0.22). The association between the levels of attitude and that of practice was non-significant (χ2 = 0.29 p = 0.59). The judokas of developing countries like those in southern Benin would benefit from specific training and participation in more competitions to improve their practice regarding MR and their sports performance.